KEPENTINGAN AMERIKA SERIKAT DALAM UPAYA MEMPERBAIKI HUBUNGAN BILATERAL JEPANG – KOREA SELATAN PASCA DISTORSI SEJARAH - M. Fauzi A.; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to determine about interests of the United States in an effort to improvebilateral relations of Japan adn South Korea post distortion of history .Type of this research isdescriptive analysis.Japan and south Korea are the two countries that have egos to be able tocarry out bilateral cooperation, this is due to historical factors. Japan is a country tateverinvaded south korea and caused reluctance to cooperate with japanese. United states as an allyof both countries try to take a role in the problem occured, the author tries to explain detailabout what the American interest in improving relations between the two countries.Sources to bepresented in this research is secondary sources.Sources were obtained through literature review, other books, internet, ect. The sources analysisisqualitativeanalysis.This research uses a level analysis of nation-state , use perspective thatdescribes of national interest. The national interest is a purpose, expectations, and goals to beachieved by country.The conclusions of this research the interest that is To maintain stability and security in theregion to maintain position as the country’s sole hegemony in the world., as well as reducing theinfluence of north korea and Cina especially as countries have different ideologies. This isbecause japan and south korea is an American stronghold in the East Asia region.Key word : National Interest, nation – state, distortion of history